Clinical Significance of Tumor Grade in Triple-Negative Breast Cancer: A Retrospective Cohort Analysis - Neya Ramanan; Mah-noor Malik; Sarang Upneja; Haniya Farooq; Swati Kulkarni; Rasna Gupta; John Mathews; Abdullah Nasser; Alina Bocicariu; Laurice Arayan; Lisa Porter; Bre-Anne Fifield; et al. (Biomedicines)
Triple-negative breast cancer (TNBC) is a heterogeneous cancer that lacks estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (HER2) proteins. Here, we investigated the prognostic value of grade in patients with TNBC. Methods: This retrospective study analyzed 780 TNBC patients from two large regional cancer programs in Canada. Patients seen between 1 January 2004 and 31 December 2022 were included. Patients with grade 1 tumors and stage IV disease were excluded from analysis. Demographic information regarding the patient, tumor, and treatment were collected. The primary outcomes, relapse-free survival (RFS) and overall survival (OS), were analyzed using the Cox proportional hazards model and max-combo test. Results: For patients with grade 2 TNBC, median RFS was 14.1 years (95% CI, 9.48 to not reached (NR)) while it was not reached for patients with grade 3 tumors. No difference for relapse was identified in the first five years. Beyond 5 years, 4.9% of the patients with grade 2 tumors and 1.6% of those with grade 3 tumors relapsed (p = 0.006). In that same study period, 10.4% of patients with grade 2 tumors and 5.7% of those with grade 3 tumors died (p = 0.03). Conclusion: Grade 2 TNBC was associated with a higher risk of relapse and death after the 5-year mark compared to grade 3 TNBC. This distinct pattern of relapse and survival in grade 2 TNBC, characterized by an increased risk of relapse and mortality after 5 years, warrants confirmatory investigations.